2020
DOI: 10.1007/s00508-020-01758-y
|View full text |Cite
|
Sign up to set email alerts
|

The positive effect of spermidine in older adults suffering from dementia

Abstract: SummaryThe worldwide prevalence of dementia is estimated at 35.6 million and will rise to 115 million by 2050. There is therefore an urgent need for well-founded dementia diagnostics and well-researched therapeutic options. Previous studies have highlighted that spermidine has the ability to trigger the important process of dissolving amyloid-beta plaques by autophagy. They also confirmed that nutritional intervention with the natural polyamine spermidine can prevent memory loss in aging model organisms. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 17 publications
(18 reference statements)
0
34
1
Order By: Relevance
“…Subsequently, ALDH3 synthetases synthesize β -alanine with β -aminopropion aldehyde. Previous studies confirmed that spermidine could trigger the autophagy process [ 23 , 24 ]. Considering the close association between spermidine and autophagy, we further investigated whether changes in spermidine affect autophagy.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Subsequently, ALDH3 synthetases synthesize β -alanine with β -aminopropion aldehyde. Previous studies confirmed that spermidine could trigger the autophagy process [ 23 , 24 ]. Considering the close association between spermidine and autophagy, we further investigated whether changes in spermidine affect autophagy.…”
Section: Resultsmentioning
confidence: 72%
“…In this current study, spermidine, as a major metabolite involved in β -alanine metabolism and arginine and proline metabolism pathways, was observed to be significantly increased in noise-exposed mice. Previous studies confirmed that spermidine could trigger autophagy [ 23 , 24 ]. Nowadays, increasing evidence indicates that autophagy is implicated in a great number of crucial physiological processes and involved in extensive diseases, including inflammation, cancer, neurodegenerative diseases, and cardiovascular diseases [ 34 ].…”
Section: Discussionmentioning
confidence: 71%
“…This anti-aging effect may be associated with its ability for restoring cellular metabolic dysfunction. A study of 85 elder adults reveals that spermidine significantly improved cognitive performance ( 150 , 151 ).…”
Section: The Epigenetic Intervention Strategies Of Vascular Agingmentioning
confidence: 99%
“…The same extract was previously found to be safe in mice and older humans, while not provoking changes in vital signs in the latter after 3 months ( 201 ). Another study supplemented spermidine via wheat-germ containing bread rolls (3.3 mg spermidine/piece, ~23 pieces/month) for 3 months to older adults living in nursing homes and found subtle improvements in cognitive function of patients with mild dementia ( 202 ).…”
Section: Polyaminesmentioning
confidence: 99%